PENGARUH MOTOR RELEARNING PROGRAMME TERHADAP KEMAMPUAN BERJALAN PASIEN HEMIPARESE POST STROKE DI RSUD SALEWANGANG MAROS - Intan Eddy Parindingan; Hasnia Ahmad (Politeknik Kesehatan Makassar, 2021)
Background: Stroke is a world health problem with an annual incidence of 0.2 – 2.5 per 1000 population. Hemiparese is a motor control disorder that appears after a stroke. These motor disturbances are associated with reduced walking speed with changes in walking time and distance traveled. Patients with hemiparesis tend to take short, uneven steps and spend a longer time standing on the side of the body that is not experiencing weakness.Methods: This research is a type of pre-experimental research with a pre test-post test one group design, aiming to determine the effect of the Motor Relearning Program on the walking ability of hemiparese post stroke patients at Salewangang Maros Hospital, with a sample of 14 people who received motorbike treatment Relearning Program and using the Time Up and Go (TUG) Test.Results: Based on the results of the Wilcoxon test analysis, namely p value = 0.000 at a distance of 2 meters (p <0.05), p value = 0.001 at a distance of 8 meters (p <0.05) and value of p = 0.001 at a distance of 10 meters (p <0.05), indicating that the administration of the Motor Relearning Program had an effect on increasing the ability to walk in hemipraese post stroke patients.Conclusion: The administration of the Motor Relearning Program intervention has an effect on increasing the walking ability of hemipraese post stroke patients. Patients are advised to apply this exercise daily to improve their walking ability.Keywords: Motor Relearning Program, Ability to walk, Stroke